(untitled) (Revista de História da UEG (REVHIST), 2022)
Motherhood, especially throughout the 20th century, was a condition on which strong social attacks were carried out from female minds and bodies. Those who were distant from the model of woman based on marriage, motherhood and dedication to the home, were incorporated into the field of the different, unfeasible and, often, pathological. However, as the 21st century approached, it became increasingly unsustainable to keep these women in the field of the unseen, so this study proposes to analyze the representations about the non-exercise of motherhood from the reports of the magazine Pais & Filhos, a journal of national circulation that focused on female mothers, under the time frame from 1969 to 1972. The analysis focuses on the view incorporated by the journal regarding the non-development of maternal activity, addressing varied aspects of this condition, such as the issue of the relationship with work and health based on themes about abortion and contraception, issues that are intertwined at the heart of the non-maternal condition[1]. Keywords: History. Gender. Not motherhood. Parents & Sons Magazine. [1]This text is the result of a monographic work of completion of the Undergraduate Course in Full History degree developed and approved in 2021 at the State University of Piauí- UESPI.